Mesenchymal Stem Cell Therapy for Doxorubicin-Induced Cardiomyopathy: Potential Mechanisms, Governing Factors, and Implications of the Heart Stem Cell Debate - Abushouk, Abdelrahman Ibrahim; Salem, Amr Muhammad Abdo; Saad, Anas; Afifi, Ahmed M.; Afify, Abdelrahman Yousry; Afify, Hesham; Salem, Hazem S.E.; Ghanem, Esraa; Abdel-Daim, Mohamed M. (Frontiers in Pharmacology, 2019)
Over the past decades, researchers have reported several mechanisms for doxorubicin (DOX)-induced cardiomyopathy, including oxidative stress, inflammation, and apoptosis. Another mechanism that has been suggested is that DOX interferes with the cell cycle and induces oxidative stress in C-kit+ cells (commonly known as cardiac progenitor cells), reducing their regenerative capacity. Cardiac regeneration through enhancing the regenerative capacity of these cells or administration of other stem cells types has been the axis of several studies over the past 20 years. Several experiments revealed that local or systemic injection with mesenchymal stem cells (MSCs) were associated with significantly improved cardiac function, ameliorated inflammatory response, and reduced myocardial fibrosis. They also showed that several factors can affect the outcome of MSCs treatment for DOX cardiomyopathy, including the MSCs type, dose, route, and timing of administration. However, there is growing evidence that the C-kit+ cells do not have a cardiac regenerative potential in the adult mammalian heart. Similarly, the protective mechanisms of MSCs against DOX-induced cardiomyopathy are not likely to include direct differentiation into cardiomyocytes and probably occur through paracrine secretion, antioxidant and anti-inflammatory effects. Better understanding of the involved mechanisms and the factors governing the outcomes of MSCs therapy is essential before moving to clinical application in patients with DOX-induced cardiomyopathy.